Sero-prevalence of HIV, HBV, HCV in Blood Specimens Received at a Clinical Laboratory in Atbara, Sudan - Elmadhoun, Wadie Mohamed Yasin; Ibrahim, Mohamed Ahmed; Musa, Hassan Abdelaziz (مجلة الجزيرة للعلوم الصحية; مجلد 8 عدد 2 (2012), 2012)
Background: Clinical laboratory personnel, like all healthcare workers, have a high risk of occupational exposure to blood-borne infections from clinical specimens, more so in developing countries, where unsafe practices are common. The most common and important ones are HIV ,HBV, and HCV infections. Objectives : To determine the sero-prevalence of HIV, HBV and HCV infections in blood samples at a clinical laboratory, and to address the preventive measures. Methods : Blood samples of 385 subjects attended for investigations of noninfectious illnesses were tested for the  seroprevalence of HIV, HBV, and HCV by screening tests and confirmed by ELISA.  Results : Males constituted 63.9%, HIV was confirmed in 0.5%, HBV in 7.8% and HCV in none of the study population. Conclusion : The risk of blood borne viral disease in blood specimens is remarkable even in non-suspected specimens and protective measures against occupational exposure must be taken in order to prevent infection among laboratory  workers.